A Novel Plant‐Based Food to Enlarge the Access of Healthy Bioactive Compounds Typical of the Mediterranean Diet to Non‐Adherent People - Andrea Polo; Francesco Maria Calabrese; Ali Zein Alabiden Tlais; Ilario Ferrocino; Francesca De Filippis; Giuseppe Celano; Olimpia Vincentini; Vincenzo Valentino; Cristian Del Bo'; Simona Bo; Raffaella Di Cagno; Luca Simone Cocolin; et al. (Food Frontiers, 2025)
ABSTRACT We selected ingredients with a high content of bioactive components typical of the Mediterranean diet (MD) and designed an MD‐based food. Its effect on human gut microbiota, microbiome, and metabolome was explored in comparison to placebo by feeding a Twin Mucosal Simulator of the Human Intestinal Microbial Ecosystem (Twin M‐SHIME). The fecal donor used for the inoculation of the Twin M‐SHIME was chosen within a cohort of individuals showing low adherence to MD. The administration of MD‐based food increased the abundance of numerous taxa, almost all having the potential to exert beneficial activities. The reshaping of the microbiota reflected on microbiome changes: genes responsible for colanic acid biosynthesis (implicated in healthy aging) and carbohydrate metabolism increased, whereas genes involved in l‐valine pathway decreased. MD‐based food temporarily increased short‐chain fatty acid (SCFA) synthesis, reflecting the increase of genes responsible for butyrate synthesis and fiber degradation. MD‐based food modulated the synthesis of volatile organic compounds (VOCs), mainly esters derived from medium‐ and long‐chain fatty acids and polyunsaturated fatty acids.